Ophiopogonin D increase apoptosis by activating p53 via ribosomal protein L5 and L11 and inhibiting the expression of c-Myc via CNOT2 - Ko, Hyun Min; Jee, Wona; Lee, Duckgue; Jang, Hyeung-Jin; Jung, Ji Hoon (Frontiers in Pharmacology, 2022)
Ophiopogonin D (OP-D), which is extracted from the root tuber of Ophiopogon japonicus, is well known for its anti-inflammatory, anti-oxidant, and anti-cancer effects. It is also therapeutic for various diseases such as diabetic myocardial injuries, obesity, atopic dermatitis, and osteoporosis. However, there are insufficient reports on the anti-cancer effects and molecular mechanisms of OP-D in colorectal cancer. Therefore, this study aimed to investigate the anti-cancer-modulating effect of OP-D on colorectal cancer. The study proved that OP-D (20–40 uM) has significant cell viability inhibition and anti-proliferative effects in Cell Counting Kit-8 (CCK-8) assay and colony formation assay. In addition, our immunofluorescence analysis data showed that OP-D (40 uM) inhibited the expression of Ki67, a cell proliferation marker, and confirmed that OP-D could induce nucleolar stress by depletion of IPO7 and XPO1. Furthermore, our western blot data showed that OP-D induced p53 expression via ribosomal protein (RP) L5 or L11 and inhibited c-Myc expression through CNOT2 in a dose-dependent manner. Additionally, OP-D regulated cyclin D1 and CDK4, which are well known as cell cycle regulatory proteins. OP-D consistently inhibited the phosphorylation of AKT expression in a dose-dependent manner. Furthermore, OP-D shortened c-Myc’s half-life in a time-dependent manner. Furthermore, CNOT2 knockdown enhanced the inhibitory effect of OP-D on c-Myc in colon cancer cells. Besides that, we confirmed that OP-D has a combinational anti-cancer effect of 5-FU or doxorubicin to reduce cell viability and induce apoptosis through p53 and c-Myc regulation. Altogether, our results suggest that OP-D regulates colon cancer cell proliferation and induces apoptosis by inhibiting c-Myc expression via activation of p53 and CNOT2 regulation. The study demonstrated that OP-D may be a promising natural anti-cancer agent for the treatment of colorectal cancer.